2013
DOI: 10.1016/j.yqres.2013.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Lake Agassiz during the Younger Dryas

Abstract: Lake Agassiz was ponded on the northward-sloping surface of the Hudson Bay and Arctic Ocean basins, as the Laurentide Ice Sheet retreated. The level of Lake Agassiz abruptly fell ~ 12.9 cal (11 14C) ka BP, exposing the lake floor over a large region for > 1000 yr. The routing of overflow during this (Moorhead low-water) period is uncertain, and there is evidence on the continent and in ocean basins for both an easterly route through the Great Lakes–St. Lawrence to the North Atlantic and for a northwesterly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 92 publications
(128 reference statements)
3
26
0
Order By: Relevance
“…Dixon, 1999;Goebel et al, 2008;Eriksson et al, 2012;Pedersen et al, 2016), but also in relation to the routing of meltwater from Glacial Lake Agassiz (Smith and Fisher, 1993;Fisher and Smith, 1994;Fisher et al, 2002;Tarasov and Peltier, 2005;Murton et al, 2010;Fisher and Lowell, 2012;Teller, 2013; see Section 3.3). The rapid collapse of the saddle between the LIS and CIS has also been hypothesised as a potential source of meltwater pulse 1A (Gregoire et al, 2012(Gregoire et al, , 2015a, although the precise contributions from North America are subject to ongoing debate Carlson and Clark, 2012;Deschamps et al, 2012).…”
Section: Late Glacialmentioning
confidence: 99%
“…Dixon, 1999;Goebel et al, 2008;Eriksson et al, 2012;Pedersen et al, 2016), but also in relation to the routing of meltwater from Glacial Lake Agassiz (Smith and Fisher, 1993;Fisher and Smith, 1994;Fisher et al, 2002;Tarasov and Peltier, 2005;Murton et al, 2010;Fisher and Lowell, 2012;Teller, 2013; see Section 3.3). The rapid collapse of the saddle between the LIS and CIS has also been hypothesised as a potential source of meltwater pulse 1A (Gregoire et al, 2012(Gregoire et al, , 2015a, although the precise contributions from North America are subject to ongoing debate Carlson and Clark, 2012;Deschamps et al, 2012).…”
Section: Late Glacialmentioning
confidence: 99%
“…Teller et al, 2000;Lepper et al, 2013); (3) data-calibrated numerical ice sheet modelling (Tarasov and Peltier, 2006); (4) the palaeo-topography of the basin inferred from isostatic rebound (e.g. Leverington et al, 2000;2002;Rayburn and Teller, 2007); and (5) the dating of meltwater events in the different outlet channels, and in lakes and oceans beyond the channel mouths (Section 2.6), including the use of deep sea oxygen isotope records and distinctive sediment discharge to identify meltwater pulses (Fisher, 2007;Hillaire-Marcel et al, 2008;Lowell et al, 2009;Lewis et al, 2012;Fisher and Lowell, 2012;Teller, 2013).…”
Section: Proglacial Hydrology Of Ice Sheets and Proglacial Lakesmentioning
confidence: 99%
“…It has been argued that overflow from GLA may have triggered the YD stadial, but there is uncertainty as to whether it overflowed to the east, to the northwest, or did not overflow at all (Lowell et al, 2009;Fisher and Lowell, 2012;Lowell et al, 2013;Teller, 2013). Opinions differ about precise timing and routing of GLA overflow during the YD, because different approaches often yield different interpretations (e.g.…”
Section: Proglacial Hydrology Of Ice Sheets and Proglacial Lakesmentioning
confidence: 99%
See 1 more Smart Citation
“…In his review of the literature about Lake Agassiz, Teller (2013) concluded that the question as to which path the Lake Agassiz floodwaters took has not been resolved yet. It might simply be that evidence for a large catastrophic drainage event is lacking, unless the meltwater drainage did occur subglacially as proposed by Livingstone et al (2013), in which case, no such sedimentary evidence will be found.…”
Section: Lawrence Routingmentioning
confidence: 99%